Inflammatory cells in the airways in COPD. Issue 5 (28th April 2006) - O'Donnell, R; Breen, D; Wilson, S; Djukanovic, R
Abstract : Airway inflammation is central to the pathogenesis of both airway remodelling and parenchymal destruction in chronic obstructive pulmonary disease (COPD). Neutrophils, macrophages, and CD8+ T lymphocytes have been implicated in a number of studies, but a detailed profile of disease-phenotype specific inflammation has yet to emerge. The heterogeneity of the disease has hindered data interpretation while extrapolation of the results of relatively non-invasive studies to the actual pathology found in the distal lung is difficult. Moreover, prominent studies have had frequently conflicting results. Further investigations are needed to marry the different clinical phenotypes of COPD to their respective inflammatory profiles in the airways and thus improve our understanding of the pathogenesis of the disease as a whole.